Pengaruh Return on Equity Ratio dan Debt Equity Ratio terhadap Price Earning Ratio pada Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016 - Arif Hidayat; Agus Suhartono; Sari Karmiyati (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of Return On Equity Ratio and Debt Equity Ratio on Price Earning Ratio in Cigarette Companies Listed on the Indonesia Stock Exchange for the period 2012-2016. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study Return On Equity Ratio has a significant effect on Price Earning Ratio of 43.2%, hypothesis testing obtained significance (Sig.) 0.002 <0.05. The Debt Equity Ratio has no significant effect on the Price Earning Ratio of 00.1%, hypothesis testing is obtained with a significance of (Sig.) 0.991 > 0.05. Return On Equity Ratio and Debt Equity Ratio simultaneously have a significant effect on Price Earning Ratio with the regression equation Y = 14,324 + 23.699X1 + -2,020X2 and the contribution of the influence is 59.6%, hypothesis testing is obtained Significance (Sig.) 0.000 < 0, 05.